A New Binding Assay of von Willebrand Factor and Glycoprotein Ib Using Solid-Phase Biotinylated Platelets - Kenji Hayata; Takayuki Nakayama; Tadashi Matsushita; Katsuichi Sakano (Elsevier, 2008)
To obtain compounds that inhibit the interaction of von Willebrand factor (vWF) and glycoprotein (GP) Ib, a novel binding assay was established. The binding of fixed platelets to vWF-R497 mutant was quantified by a solid phase assay. In this assay, fixed platelets bound to the vWF-R497 mutant, carrying the deletion of Glu497-Tyr508 and the missense mutation of Arg545 to Ala, without binding modulators such as ristocetin. The Kd value of the binding was 2.8 nM, which was consistent with the result from liquid binding assay. The binding was inhibited by aurin tricarboxylic acid (ATA) and an anti GPIb antibody, AK2. Using this binding assay, we screened our library compounds and obtained D74-3736. This compound also inhibited ristocetin-induced platelet aggregation in the human platelet-rich plasma. Keywords:: biotinylation of fixed platelets, binding assay of von Willebrand factor (vWF) to glycoprotein Ib (GPIb)